Role of Magnetic Resonance Imaging in Diagnosing Neurological Complications in Intermediate Syndrome of Organophosphate Poisoning - Ravikanth, Reddy (Indian J Crit Care Med, 2017)
Organophosphate poisoning (OP) is a very common mode of suicide in rural and urban areas due to the wide availability of pesticides. The identification of OP and timely referral for appropriate supportive care can be lifesaving. Injury to the central nervous system is a serious entity in acute OP. Application of modern imaging techniques like diffusion weighted imaging increases the diagnostic rate of brain injury in the early period and can provide evidence for medical treatment. We present the imaging features in the intermediate syndrome of OP.